Security Enhancement in Mobile Adhoc Networks using computational intelligence - Anithaashri, T.P.; M.Saravanan (International Journal of Psychosocial Rehabilitation, 2020)
Mobile Adhoc Networks (MANET) is a collection of wireless nodes that can dynamically form network to exchange information without using any fixed network infrastructure. By using advanced technology in MANET provides the way to serve challenges. MANET are known to be vulnerable to a variety of attacks due to lack of central authority or fixed network infrastructure. In many more security schemes have been proposed to identify misbehaving nodes. In this paper it has been proposed an intelligence based link state routing protocol named ILSR for mobile wireless networks. Thus the protocol is based on the link state algorithm and it is proactive of its nature. It employs occasional exchange of messages to maintain topology information of each network at each node.ILSR is an improvement over a pure link state protocol as it compacts the size of information sent in the messages, and in addition, reduces there number of retransmissions to these messages in entire network.. They provide optimal security solution to the current scenario in large and dense ad hoc networks.